From flood to turbidity current: combined models to simulate continent to ocean sediment transport in the Var system, France - Arthur Remaud; John J. Armitage; Vanessa Teles; Sébastien Rohais; Thierry Mulder (Sedimentologika)
Turbidity currents are a form of gravity-driven flow that occurs in subaqueous environments. These currents contain a low volumetric percentage of particles but are very important in transporting them from coastal to deep-marine environments. In the Var sediment routing system, southeastern France, there is a sedimentary record of turbidity currents formed by submarine landslides and flooding of the Var River. In 2006, there was continuous monitoring of the marine section that recorded four turbidity currents. To explore the connectivity between the terrestrial source and marine basin we linked two reduced complexity models of sediment transport and landscape change. The aim of the paper is to combine two models, one dedicated to the prediction of river water and sediment run-off, and the second dedicated to the transport, erosion, and sedimentation by a turbidity current. The landscape evolution model CAESAR-Lisflood was used to model discharge and sediment yield. The behaviour of turbidity currents was modelled with the cellular automata model CATS. From calibration of the two models against observations of discharge and suspended sediment in the Var River system, we find that in 2006, two rainfall events would have led to hyperpycnal turbidity currents. These two events match well with two of the four-recorded events. Focusing on the largest event we find that the source pulse of sediment from the terrestrial environment is short-lived, less than half a day, but contains a significant quantity of fine particles. The event transferred on the order of 105 m3 of suspended sediment from source to sink. This study demonstrates that hyperpycnal turbidity currents can be generated with concentrations as low as 2-6 kg/m3 at the Var River mouth far below the theoretical 40 kg/m3 threshold, suggesting active convective sedimentation in the surface plume and sea-water dilution at the flooding river mouth. A substantial amount of sediment (35% of the input volume) is directly transferred towards the deepest part of the system during a short-living hyperpycnal turbidity current. However, a considerable (65%) part remains in the surface as a hypopycnal plume feeding the hemipelagic sedimentation.